ANALISIS KESALAHAN SISWA DALAM MENGERJAKAN SOAL MATERI BANGUN DATAR PADA LUAS LAYANG-LAYANNG DAN TRAPESIUM PADA SISWA KELAS V SDN 33 KALUMBUK KOTA PADANG - Parwines, Zutri; Hendriani, Maifit (Jurnal Riset Pendidikan Dasar Dan Karakter, 2022)
This study aims to describe the types of student errors in solving problems about flat shapes on the area of a trapezoid and a kite. This type of research is descriptive qualitative research. Collecting data in this study through a written description test on the kite and trapezoidal shape material. The research subjects were fifth-grade students of SDN 33 Kalumbuk, Padang city. The research instrument was in the form of a test sheet containing questions about the kite and trapezoidal shapes and interview guidelines. Data were analyzed descriptively. Based on the data analysis, it was found that the problem was the students' lack of understanding of addition, multiplication, and division. The results of this study can be used as material for developing student problems, especially in the area of trapezoidal marries and kites in the future.